Transmission of cultural traits in layered ego-centric networks - Palchykov, V.; Kaski, K.; Kert\'esz, J. (Condensed Matter Physics, 2014)
Although a number of models have been developed to investigate the emergence of culture and evolutionary phases in social systems, one important aspect has not yet been sufficiently emphasized. This is the structure of the underlaying network of social relations serving as channels in transmitting cultural traits, which is expected to play a crucial role in the evolutionary processes in social systems. In this paper we contribute to the understanding of the role of the network structure by developing a layered ego-centric network structure based model, inspired by the social brain hypothesis, to study transmission of cultural traits and their evolution in social network. For this model we first find analytical results in the spirit of mean-field approximation and then to validate the results we compare them with the results of extensive numerical simulations. Хоча було розвинено ряд моделей для дослiдження появи культури та еволюцiйних фаз у соцiальних
системах, один важливий аспект не був достатньо висвiтлений. Цим аспектом є роль структури мереж
соцiальних зв’язкiв, якi служать каналами для передачi культурних особливостей i якi вiдiграють важливу
роль в еволюцiйних процесах у соцiальних системах. У данiй статтi ми дослiджуємо цю роль у моделi
переачi культурних особливостей та їх еволюцiю в соцiальних системах, спираючись на пластоподiбнi
структури егоцентричних мереж, надхненi гiпотезою соцiального мозку. Для цiєї моделi ми отримали
аналiтичний розв’язок у дусi середнього поля та дослiдили його застосовнiсть, порiвнюючи отриманi
передбачення з результатами чисельних симуляцiй.